Standard Death Certificates Versus Enhanced Surveillance to Identify Heroin Overdose–Related Deaths - Horon, Isabelle L. (Am J Public Health, 2018)
Objectives. To compare 2 approaches to identifying heroin-related deaths in cases of overdose: standard death certificates and enhanced surveillance. Methods. We reviewed Maryland death certificates from 2012 to 2015 in cases of overdose to determine specific mentions of heroin. Counts were compared with estimates obtained through an enhanced surveillance approach that included a protocol considering cause of death, toxicology, and scene investigation findings. Results. Death certificates identified 1130 heroin-related deaths. Enhanced surveillance identified 2182 cases, nearly double the number found through the standard approach. The major factors supporting enhanced surveillance in identifying cases were the presence of morphine, either alone or in combination with quinine, and scene investigation information suggesting heroin use. Conclusions. Death certificates, the primary source of state and national data on overdose deaths, may underestimate the contribution of heroin to drug-related mortality. Enhanced surveillance efforts should be considered to allow a better understanding of the contribution of heroin to the overdose crisis. Public Health Implications. If enhanced surveillance can be incorporated into the death certificate process, national data on overdoses may better reflect the contribution of heroin to the opioid crisis.